DIAGNOSTIC ACCURACY OF ULTRASOUND SONOGRAPHY TEST AND COMPUTED TOMOGRAPHY COMPARED WITH MAGNETIC RESONANCE CHOLANGIO PANCREATOGRAPHY IN PATIENTS WITH OBSTRUCTIVE JAUNDICE CONSIDERING ENDOSCOPIC RETROGRADE CHOLANGIO PANCREATOGRAPHY AS GOLD STANDARD - Khalid, Muhammad Sehran; Sadaf Arooj; Awais Ahmed; Ali Mansoor; Mahjabeen Masood (Journal of Postgraduate Medical Institute, 2023)
Objective: To determine the diagnostic accuracy of USG and CT compared with MRCP in the patients with obstructive jaundice considering ERCP as the gold standard Methodology: This cross-sectional study at Mayo Hospital, Lahore, spanned 6 months and included 71 cases meeting predefined criteria. A senior radiologist prepared all reports. The study used preliminary ultrasound, CECT abdomen, and MRCP for patients with cholestatic jaundice, comparing results with ERCP. MRCP showed higher diagnostic accuracy. Results: MRCP proved to be the most accurate in diagnostic accuracy. Its sensitivity and specificity for benign conditions were 94.87% and 93.75% while for CT it was 87.18% and 81.25% and for USG it was 84.62% and 90.63% respectively. For malignant conditions sensitivity and specificity for MRCP was 93.75% and 97.44% for CT it was 87.5% and 92.31% and for USG it was 81.25% and 89.74% respectively. Conclusion: The results of this study demonstrate that MRCP is a superior modality, exhibiting higher sensitivity, specificity, and diagnostic accuracy for evaluating both malignant and benign conditions in patients with obstructive jaundice compared to USG and contrast-enhanced CT. MRCP's specificity for various etiologies matches that of ERCP, which is considered the gold standard. While MRCP's cost and availability may be a concern, its non-invasiveness, contrast-free nature, and high diagnostic accuracy make it an ideal choice for evaluating patients with obstructive jaundice.